In Silico Insight of Natural Compounds in Ageratum Conyzoides L as Anti Breast Cancer Candidate by Molecular Docking Against EGFR - Tjitda, Putra Jiwamurwa Pama; Wahyuningsih, Tutik Dwi; Nitbani, Febri Odel (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2024)
The regulation of proliferation and apoptosis in cancer cells, particularly breast cancer, hinges on the control exerted by the epidermal growth factor receptor (EGFR). Naturally derived EGFR inhibitors from natural compounds show significant potential for future advancements. This study aims to assess the efficacy of active compounds found in Ageratum Conyzoides L as EGFR inhibitors. Evaluation involved molecular docking studies of flavonoid, chromene, terpene, sterol, and acid compounds against EGFR using PDB ID 1m17. Additionally, the ADMET properties and drug-like characteristics of the most promising compounds were characterized. Findings reveal that compound C2 (fisetin) exhibits the most favorable binding energy of -8.9 kcal/mol. Fisetin establishes crucial interactions, particularly with the catalytic site at Met765 of the hinge protein. Fisetin also engages in hydrophobic interactions in regions I and II, involving Val702, Leu694, and Leu820. ADMET profiling of fisetin demonstrates favorable attributes, suggesting its potential as a promising anticancer agent based on drug-likeness assessments.